2012
DOI: 10.1186/1472-6963-12-372
|View full text |Cite
|
Sign up to set email alerts
|

The cost of first-ever stroke in Valle d’Aosta, Italy: linking clinical registries and administrative data

Abstract: BackgroundStroke is one of the most relevant reasons of death and disability worldwide. Many cost of illness studies have been performed to evaluate direct and indirect costs of ischaemic stroke, especially within the first year after the acute episode, using different methodologies.MethodsWe conducted a longitudinal, retrospective, bottom-up cost of illness study, to evaluate clinical and economic outcomes of a cohort of patients affected by a first cerebrovascular event, including subjects with ischaemic, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
11
1
4
Order By: Relevance
“…On the other hand, due to the nondisabling nature of TIA, these patients are more commonly managed as outpatients than inpatients and incur lower overall healthcare costs, which was confirmed by the regression analysis in the present study. Consistent with our study finding, the general consensus was that hemorrhagic strokes were more costly than IS and TIA , given the frequent need for neurosurgery and intensive monitoring with high levels of subsequent morbidity .…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, due to the nondisabling nature of TIA, these patients are more commonly managed as outpatients than inpatients and incur lower overall healthcare costs, which was confirmed by the regression analysis in the present study. Consistent with our study finding, the general consensus was that hemorrhagic strokes were more costly than IS and TIA , given the frequent need for neurosurgery and intensive monitoring with high levels of subsequent morbidity .…”
Section: Discussionsupporting
confidence: 89%
“…(70,3%-78%) dari subyek penelitian 7,24,25,26 . Adanya beberapa faktor resiko stroke yang tidak dapat dimodifikasi seperti usia, jenis kelamin, ras dan riwayat keluarga serta efek kumulatif penuaan pada sistem kardiovaskular dan serebrovaskular, dan sifat progresif dari faktor resiko stroke selama periode waktu yang lama secara substansial meningkatkan resiko stroke.…”
Section: Hasil Dan Pembahasanunclassified
“…Despite some limitations of our findings and of our method, we have also demonstrated that our algorithm, based on administrative data, can accurately identify patient cohorts. Our future aims are to investigate the geographical distribution of MS in Tuscany and to create an integrated dataset with administrative and clinical data to monitor not only prevalence but also disease-care pathways and proxy to outcomes [36,37,38]. …”
Section: Discussionmentioning
confidence: 99%